2024
DOI: 10.1101/2024.02.26.582161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of enriched versus depleted housing on eucalyptus smoke-induced cardiovascular dysfunction in mice

Molly E. Harmon,
Michelle Fiamingo,
Sydnie Toler
et al.

Abstract: Living conditions play a major role in health and well-being, particularly for the cardiovascular and pulmonary systems. Depleted housing contributes to impairment and development of disease, but how it impacts body resiliency during exposure to environmental stressors is unknown. This study examined the effect of depleted (DH) versus enriched housing (EH) on cardiopulmonary function and subsequent responses to wildfire smoke. Two cohorts of healthy female mice, one of them surgically implanted with radiotelem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…We compared enriched housing, which includes several forms of environmental enrichment, with depleted housing to evaluate the role of non-chemical stressors like living conditions in modifying physiological resiliency to a single smoke exposure. Our previous work showed that enriched housing improves cardiovascular outcomes, speci cally a lower heart-rate, during and after a wild re smoke exposure and promotes an increase in the expression of cardioprotective genes in the left ventricle [27]. The current study expanded this approach to assess whether housing alters cardiovascular function in atherosclerotic-prone mice and whether the effects are sex-speci c. We found that the effect of housing on baseline cardiovascular function and the cardiovascular response to WS in ApoE (-/-) mice occurs in a sex-speci c manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared enriched housing, which includes several forms of environmental enrichment, with depleted housing to evaluate the role of non-chemical stressors like living conditions in modifying physiological resiliency to a single smoke exposure. Our previous work showed that enriched housing improves cardiovascular outcomes, speci cally a lower heart-rate, during and after a wild re smoke exposure and promotes an increase in the expression of cardioprotective genes in the left ventricle [27]. The current study expanded this approach to assess whether housing alters cardiovascular function in atherosclerotic-prone mice and whether the effects are sex-speci c. We found that the effect of housing on baseline cardiovascular function and the cardiovascular response to WS in ApoE (-/-) mice occurs in a sex-speci c manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have focused on characterizing changes in cardiovascular physiology and function from housing enrichment and the ability of housing to modulate resiliency against an air pollution exposure. Our previous work showed that depleted housing causes increased heart rate, incidence of arrhythmias, and lower activity levels in healthy mice during a single smoke exposure [27]. However, the effect of this housing paradigm on underlying CVD and the corresponding response to WS remains unknown.…”
mentioning
confidence: 99%